Effects of Gastric Bypass Surgery on Bone Mass and Microarchitecture Occur Early and Particularly Impact Postmenopausal Women - Schafer, Anne L. (J Bone Miner Res, 2018)
Roux-en-Y gastric bypass (RYGB) surgery is a highly effective treatment for obesity but negatively affects the skeleton. Studies of skeletal effects have generally examined areal BMD by DXA, but DXA may be inaccurate in the setting of marked weight loss. Further, as a result of modestly sized samples of mostly premenopausal women and very few men, effects of RYGB by sex and menopausal status are unknown. We prospectively studied the effects of RYGB on skeletal health, including axial and appendicular volumetric BMD and appendicular bone microarchitecture and estimated strength. Obese adults (N=48; 27 premenopausal and 11 postmenopausal women, 10 men) with mean ±SD BMI 44 ±7 kg/m(2) were assessed before and 6 and 12 months after RYGB. Participants underwent spine and hip DXA, spine QCT, radius and tibia HR-pQCT, and laboratory evaluation. Mean 12-month weight loss was 37 kg (30% of preoperative weight). Overall median 12-month increase in serum CTx was 278% (p<0.0001), with greater increases in postmenopausal than premenopausal women (p=0.049). Femoral neck BMD by DXA decreased by mean 5.0% and 8.0% over 6 and 12 months (p<0.0001). Spinal BMD by QCT decreased by mean 6.6% and 8.1% (p<0.0001); declines were larger among postmenopausal than premenopausal women (11.6% vs. 6.0% at 12 months, p=0.02). Radial and tibial BMD and estimated strength by HR-pQCT declined. At the tibia, detrimental changes in trabecular microarchitecture were apparent at 6 and 12 months. Cortical porosity increased at the radius and tibia, with more dramatic 12-month increases among postmenopausal than premenopausal women or men at the tibia (51.4% vs. 18.3% vs. 3.0%, p<0.01 between groups). In conclusion, detrimental effects of RYGB on axial and appendicular bone mass and microarchitecture are detectable as early as 6 months postoperatively. Postmenopausal women are at highest risk for skeletal consequences and may warrant targeted screening or interventions.